Method for preparing catalyst for hydrogen production by photolysis of water by using waste titanium dioxide carrier

The waste titanium dioxide support was repaired through impregnation and pyrolysis technology, and the Cu-TiO2 photocatalyst was prepared, which solved the problems of short SCR catalyst life and insufficient performance of TiO2 photocatalysts, and achieved efficient and low-cost photocatalytic hydrogen production effect.

CN119386866APending Publication Date: 2025-02-07CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411475181.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, SCR catalyst has a short life and heavy metals, which leads to difficulty in handling waste catalysts. The traditional TiO2 photocatalyst has high cost, insufficient redox capacity, severe charge recombination, and few surfactant sites, which limits its large-scale application. .

Method used

The waste titanium dioxide support is repaired in situ through impregnation and pyrolysis technology, and the Cu-TiO2 photocatalyst is prepared to realize the resource utilization of waste TiO2 support and improve the activity of the catalyst.

Benefits of technology

The high-value utilization of waste catalysts has been achieved. The prepared Cu-TiO2 catalyst has high activity, low cost and low energy consumption, and is suitable for large-scale preparation. Its hydrogen production capacity is 1.46 times that of commercial titanium dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for preparing a catalyst for hydrogen production by photolysis of water by using a waste titanium dioxide carrier. The method for preparing the catalyst for hydrogen production through water photolysis by using the waste titanium dioxide carrier comprises the following steps: S1, dipping the waste titanium dioxide carrier in an aqueous solution of a cupric salt, and carrying out stirring treatment, so that copper is adsorbed on the surface of the carrier; wherein the mass percentage content of TiO2 in the waste titanium dioxide carrier is greater than 85%; and S2, carrying out pyrolysis treatment on the product obtained in the step S1 to obtain the catalyst for producing hydrogen by photolysis of water. According to the method, TiO2 in the waste SCR catalyst carrier is subjected to in-situ remediation to directly prepare the Cu-TiO2 photocatalytic material with excellent performance, high-valued utilization of the waste catalyst is achieved, the obtained hydrogen production catalyst has high activity, the method is integrally green and free of pollution, the raw material cost is low, the utilization rate is high, energy consumption is low, and the method is suitable for large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste carrier recovery and photocatalytic hydrogen production catalyst, and in particular to a method for preparing a photocatalytic water decomposition hydrogen production catalyst using waste titanium dioxide carrier. Background Art

[0002] Selective catalytic reduction (SCR) catalysts are widely used in power plant decommissioning systems to improve the selective reduction of flue gas nitrogen oxides and are suitable for various major industrial scenarios. However, they usually deactivate after 3-5 years, have a short lifespan, and simply disposing of spent SCR catalysts (landfill or pile) is not an economical solution due to the presence of heavy metals. The industry produces about 250,000 tons of spent SCR catalysts each year, and environmental pollution caused by deactivation has become a serious problem. In this context, the concept of "turning waste into treasure" has aroused great interest in the scientific community, that is, recovering key metals from waste materials for the production of high value-added energy materials. As a potential secondary resource, spent SCR catalysts contain 70%-90% TiO2 carriers. Repairing the TiO2 carrier in spent SCR catalysts can not only reduce environmental pressure, but also improve the utilization rate of titanium resources in raw materials and reduce the inventory of deactivated and harmful catalysts.

[0003] Photocatalytic hydrogen generation is considered to be one of the most promising clean energy sources. Traditional semiconductor photocatalysts represented by TiO2 have been widely studied by the scientific community due to their high chemical stability, environmental friendliness, good photocatalytic activity, and ease of preparation. When semiconductor nanostructures such as TiO2 are excited by photons with energy exceeding the semiconductor band gap, they use light to generate electron-hole pairs, thereby exhibiting photocatalytic properties. It decomposes water under sunlight and is considered to be the main raw material for producing green hydrogen energy. However, the high cost, insufficient redox ability, severe charge recombination, and few surface active sites of TiO2-based photocatalysts still limit their large-scale practical application.

[0004] Using the titanium resources in the in-situ repair of selective catalytic reduction (SCR) catalysts to prepare efficient TiO2 photocatalytic hydrogen production catalysts can solve the energy problem while reusing the SCR catalyst resources. There are currently no related reports. Summary of the invention

[0005] Based on the above technical problems, the purpose of the present invention is to provide a method for preparing a photocatalytic water splitting hydrogen production catalyst using waste titanium dioxide carrier. The method uses simple impregnation and pyrolysis technology to repair the titanium dioxide carrier in situ, and prepares the photocatalytic hydrogen production material Cu-TiO2 from the waste TiO2 carrier. Not only can the resource reuse of the waste TiO2 carrier be achieved, but the obtained hydrogen production catalyst has high activity. The method of the present invention is green and pollution-free, has low raw material cost, high utilization rate, low energy consumption, good effect, and is suitable for large-scale preparation.

[0006] To achieve the above object, the present invention provides a method for preparing a photocatalytic hydrogen production by water splitting using a waste titanium dioxide carrier, comprising the following steps: S1, immersing the waste titanium dioxide carrier in an aqueous solution of a divalent copper salt and stirring the solution to allow copper to be adsorbed on the surface of the carrier; Wherein, the mass percentage of TiO2 in the waste titanium dioxide carrier is greater than 85%; S2. The product obtained in step S1 is subjected to pyrolysis treatment to obtain the photocatalytic water decomposition hydrogen production catalyst.

[0007] Based on the above scheme, the present invention immerses the waste titanium dioxide carrier in a copper-containing solution and stirs to obtain a light green copper-doped titanium dioxide precursor; through high-temperature pyrolysis in a muffle furnace, the copper species moves with the waste titanium dioxide carrier at high temperature to obtain a non-precious metal copper-doped titanium dioxide photocatalyst, which shows excellent hydrogen production capacity in the test. Among them, the prepared photocatalytic hydrogen production material Cu-TiO2 represents a copper species-doped titanium dioxide material, and the existence form of the copper species is affected by the properties of the raw materials and the preparation conditions.

[0008] Furthermore, the waste titanium dioxide carrier comes from a waste SCR catalyst, and the waste SCR catalyst can be a waste catalyst obtained by denitrifying flue gas containing nitrogen oxides using any SCR catalyst with a titanium dioxide carrier; in addition to the titanium dioxide carrier, the SCR catalyst also contains one or more oxides such as V2O5, WO3, Fe2O3, NiO, CuO, MoO3, SiO2, Al2O3, etc., as active ingredients, co-active ingredients or additives; wherein, in order to convert TiO2 in the waste titanium dioxide carrier into photocatalytic hydrogen production material Cu-TiO2, the mass percentage of TiO2 in the waste titanium dioxide carrier needs to be greater than 85%, such as 86.22%, because when the mass percentage of TiO2 in the waste titanium dioxide carrier is less than 85%, the catalyst is basically inactive due to excessive impurity content.

[0009] Preferably, the waste titanium dioxide carrier is obtained according to the following steps: ultrasonically washing, drying and ball milling the waste SCR catalyst in sequence; the surface of the waste titanium dioxide carrier after pretreatment has no obvious fly ash impurities; The particle size of the waste titanium dioxide carrier is ≤45um; As an example, in the ultrasonic washing step, 5 g of the spent titanium dioxide carrier is added to every 200 ml of deionized water, and ultrasonic washing is performed multiple times, and the ultrasonic input power is 400 W; As an example, in the drying step, the mixture is dried in a forced air drying oven for 24 hours; As an example, in the grinding step, the ball-to-material ratio is set to 8:2, and after the ball milling is completed, the material is sieved through a 325-mesh screen.

[0010] Furthermore, the mass percentage of Al2O3 in the waste titanium dioxide carrier is less than 6.0%, such as 2.32%. Al2O3 itself is not an effective light absorbing material, and a high content of Al2O3 may reduce the absorption of light by TiO2 and affect the efficiency of the photocatalytic reaction.

[0011] As an example, based on the total weight of the spent titanium dioxide carrier, the composition of the spent titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0012] Furthermore, the divalent copper salt is a water-soluble copper salt, preferably copper chloride or its hydrate, more preferably at least one of anhydrous copper chloride, copper chloride monohydrate, and copper chloride dihydrate.

[0013] Furthermore, the mass ratio of the waste titanium dioxide carrier to the divalent copper salt is 1: (0.005-0.03), preferably 1: (0.008-0.0014), 1: 0.008, 1: 0.006, 1: 0.01, 1: 0.012, 1: 0.014. A too high ratio will cause a large amount of copper particles to aggregate, and a too low ratio will make it difficult for copper to be adsorbed on the catalyst surface, both of which will reduce the catalyst's hydrogen production activity.

[0014] Furthermore, the stirring treatment has a rotation speed greater than 500 r / min and a time greater than 3 hours, such as stirring at 600 r / min for 4 hours; the control of the stirring treatment time and rotation speed can make copper adsorbed on the titanium dioxide surface uniformly and with high dispersion.

[0015] Furthermore, the method comprises the following steps after the stirring treatment: centrifuging the mixture after the stirring treatment to collect the solid phase, and then washing and drying the solid phase; as an example, the centrifugal speed can be 10000r / min, and the centrifugal time is 5min; preferably, the drying is vacuum drying at 70°C for 12 to 24 hours, such as 24 hours.

[0016] Furthermore, the method further comprises the step of grinding the product obtained in step S1 before the pyrolysis treatment, preferably grinding for 0.5 to 1 hour, such as 0.5 hour; grinding can improve the uniformity of the sample, which helps to obtain a uniform heating effect and chemical reaction in the subsequent calcination process, promote solid-phase reaction and eliminate agglomeration to improve calcination efficiency: finer particles are heated more evenly during calcination, which can reduce the time and temperature required for calcination, thereby improving calcination efficiency; The pyrolysis treatment is carried out in an air muffle furnace, and the temperature is increased to 500-550°C at a heating rate of 3-10°C / min, and the holding time is 1-3h; wherein, although the heating rate will not excessively affect the combination of the copper species and the catalyst, a heating rate that is too fast or too slow may affect the oxidation rate of the material surface; the holding temperature directly affects the combination of the copper species and titanium dioxide; a short holding time may lead to uneven distribution of the copper species and weak binding force, and a long holding time may lead to excessive diffusion of the copper species in titanium dioxide, which may form larger copper clusters or copper particles, which may reduce the specific surface area and activity of the catalyst; as an example, the heating rate is 3°C / min, 5°C / min or 10°C / min; the heating temperature is 500°C or 550°C; the holding time is 2-3h, 2h or 3h.

[0017] The method further comprises a step of grinding the pyrolysis product after the pyrolysis treatment, preferably grinding for 0.5 to 1 hour, such as 0.5 hour. Grinding after calcination can increase the specific surface area of ​​the material, reduce agglomeration, provide more active sites, and help improve the photocatalytic efficiency and hydrogen production efficiency.

[0018] In a second aspect, the present invention provides a photocatalytic hydrogen production catalyst prepared by the above method. The hydrogen production capacity of the Cu / TiO2 catalyst prepared by the present invention is 1.46 times that of commercial titanium dioxide, and the hydrogen production efficiency is greatly improved.

[0019] In a third aspect, the present invention provides a method for producing hydrogen by photodecomposing water, using the photocatalytic hydrogen production catalyst as a catalyst to produce hydrogen by photodecomposing water.

[0020] Furthermore, the photocatalytic hydrogen production by water splitting comprises the following steps: placing the photocatalytic hydrogen production catalyst in a reaction solution containing water and a sacrificial agent, and irradiating it with light to generate hydrogen.

[0021] As a test example, specifically, the sacrificial agent is methanol, and 20 mg of the photocatalytic hydrogen production catalyst is uniformly dispersed in 80 mL of the reaction solution; Specifically, the volume ratio of water to methanol is 4:1; Specifically, the light uses a xenon lamp.

[0022] The present invention has the following beneficial effects: (1) A simple short-process in-situ repair process of titanium dioxide carriers was developed. The titanium dioxide carriers in the waste SCR catalysts were prepared into low-cost and high-activity photocatalysts using simple doping and pyrolysis techniques. The method of the present invention is green and pollution-free as a whole, with low raw material cost, high utilization rate, low energy consumption, good effect, and is suitable for large-scale preparation. The in-situ repair of TiO2 in the waste SCR catalyst carriers directly prepared Cu-TiO2 photocatalytic materials with excellent performance, realizing the high-value utilization of waste catalysts. By applying the high-value titanium resources in the waste SCR catalysts to the field of photocatalytic hydrogen production, a new idea with significant economic benefits is provided for the design of the reuse process of TiO2 carriers in waste SCR catalysts.

[0023] (2) The doping of copper species improves the ability of waste titanium dioxide support materials to dissociate water, broadens the light absorption range of the waste support, improves the carrier mobility, and enhances the reaction kinetics. The prepared copper-titanium dioxide catalyst has guiding significance for recycling waste materials to generate clean energy and provides new insights for alleviating the environmental pollution challenges caused by the current fossil fuel consumption.

[0024] (3) In the Cu / TiO2 catalyst prepared by the present invention, the metal copper and the semiconductor titanium dioxide are combined to form a Schottky junction, and the activity of photocatalytic water decomposition to produce hydrogen is higher. This is because: 1) From the perspective of the contact interface: when the metal contacts the semiconductor, due to the different work functions of the metal and the semiconductor, electrons will transfer from the metal with a lower work function to the semiconductor with a higher work function; this electron transfer leads to the formation of a charge depletion layer (depletion layer) at the metal-semiconductor interface, and the layer exhibits a high resistance state due to the lack of free carriers. A fixed potential difference is formed between the metal and the semiconductor. This potential difference is called a Schottky barrier, also known as a Schottky junction. The built-in electric field generated by the Schottky barrier will produce an electric field effect: it can promote charge separation and inhibit the recombination of electron-hole pairs, which is particularly critical for improving the efficiency of the photocatalytic reaction. 2) From the perspective of surface states and defect states: TiO2 in the waste SCR catalyst may contain more surface states and defect states, which can serve as additional active sites to promote charge transfer and adsorption of reactants. These surface states and defect states may help form a more effective Schottky junction, thereby improving the separation efficiency of photogenerated charges. 3) From the perspective of interface characteristics: The interface between TiO2 and Cu in the waste SCR catalyst may be rougher or irregular, which helps to increase the contact area between the metal and the semiconductor, thereby forming more Schottky junctions. The irregularity of the interface may lead to uneven local electric field distribution, which helps charge separation and migration.

[0025] (4) The hydrogen production capacity of the Cu / TiO2 catalyst prepared by the present invention is 1.46 times that of commercial titanium dioxide, and the hydrogen production efficiency is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart of preparing a catalyst for photo-decomposition of water to produce hydrogen using waste titanium dioxide carrier.

[0027] Figure 2 This is the XRD spectrum of the Cu-TiO2 sample of the photocatalytic water splitting hydrogen production catalyst prepared in Example 1 of the present invention.

[0028] Figure 3 This is a SEM image of the Cu-TiO2 sample of the photocatalytic water splitting hydrogen production catalyst prepared in Example 1 of the present invention.

[0029] Figure 4 Ultraviolet absorption spectra of the Cu-TiO2 sample of the photocatalyst for hydrogen production from water prepared in Example 1 of the present invention and the waste TiO2 carrier.

[0030] Figure 5 This is a transient photoresponse current diagram of the Cu-TiO2 catalyst for hydrogen production from photolysis of water prepared in Example 1 of the present invention and the waste TiO2 carrier.

[0031] Figure 6 This is a comparison chart of the photocatalytic hydrogen production performance of the photocatalytic water splitting hydrogen production catalyst Cu-TiO2 prepared in Example 1 of the present invention, the waste TiO2 carrier and the commercial TiO2. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0033] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0034] The spent SCR catalyst in the following examples comes from Anhui Yuanchen Environmental Protection Technology Co., Ltd.

[0035] The commercial TiO2 in the following comparative examples has a purity of 99.99% and its brand is Adamas.

[0036] Example 1 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of waste SCR catalyst, perform ultrasonication for multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry in a blast dryer for 24 hours to obtain a clean waste titanium dioxide carrier. After testing, based on the total weight of the waste titanium dioxide carrier, the composition of the clean waste titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0037] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0038] (3) Weigh 8 mg of anhydrous cupric chloride and add it to 100 ml of deionized water solution to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0039] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0040] (5) The dried product was ground in a mortar for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 3 °C / min.

[0041] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0042] The XRD pattern of the Cu-TiO2 catalyst prepared in this example is shown in Figure 2 ,from Figure 2 It can be seen that the crystal structure of the material was characterized by X-ray diffraction (XRD) spectroscopy. The strong diffraction peak near 25.3° of 2θ value in the X-ray diffraction spectrum is due to the formation of TiO2 in the standard anatase crystal form. The above test indicates that the preparation of Cu-TiO2 catalyst is successful.

[0043] SEM Figure 3 As shown in Figure 2, Cu-TiO2 has a blocky morphology. The UV-visible spectra of Cu-doped Cu-TiO2 and TiO2 carrier before doping were characterized, as shown in Figure 2. Figure 4As shown, compared with the spent TiO2 carrier, the absorption spectrum of Cu-TiO2 tends to expand towards the visible light region, indicating that the absorbance of Cu-TiO2 is enhanced.

[0044] Example 2 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of spent SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean spent titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the spent titanium dioxide carrier, the composition of the clean spent titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0045] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0046] (3) Weigh 6 mg of anhydrous cupric chloride and add it to 100 ml of deionized water solution to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0047] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0048] (5) The dried product was ground in a mortar for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 3 °C / min.

[0049] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0050] Example 3 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of spent SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean spent titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the spent titanium dioxide carrier, the composition of the clean spent titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0051] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0052] (3) Weigh 10 mg of anhydrous cupric chloride and add it to 100 ml of deionized water to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0053] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0054] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 3 °C / min.

[0055] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0056] Example 4 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of spent SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean spent titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the spent titanium dioxide carrier, the composition of the clean spent titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0057] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0058] (3) Weigh 12 mg of anhydrous cupric chloride and add it to 100 ml of deionized water solution to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0059] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0060] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 3 °C / min.

[0061] (6) Grind the powder obtained after high-temperature pyrolysis in a mortar for 30 minutes to obtain a Cu-TiO2 catalyst The properties of the catalyst material prepared in this example are shown in Table 1.

[0062] Example 5 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of waste SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean waste titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the waste titanium dioxide carrier, the composition of the clean waste titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0063] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0064] (3) Weigh 14 mg of anhydrous cupric chloride and add it to 100 ml of deionized water solution to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0065] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0066] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 3 °C / min.

[0067] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0068] Example 6 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of spent SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean spent titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the spent titanium dioxide carrier, the composition of the clean spent titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0069] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0070] (3) Weigh 8 mg of anhydrous cupric chloride and add it to 100 ml of deionized water to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0071] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0072] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 5 °C / min.

[0073] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0074] Example 7 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of spent SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean spent titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the spent titanium dioxide carrier, the composition of the clean spent titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0075] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0076] (3) Weigh 8 mg of anhydrous cupric chloride and add it to 100 ml of deionized water to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0077] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0078] (5) The dried product was ground in a mortar for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 10 °C / min.

[0079] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0080] Example 8 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of waste SCR catalyst, perform ultrasonication for multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry in a blast dryer for 24 hours to obtain a clean waste titanium dioxide carrier. After testing, based on the total weight of the waste titanium dioxide carrier, the composition of the clean waste titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0081] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0082] (3) Weigh 8 mg of anhydrous cupric chloride and add it to 100 ml of deionized water to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0083] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0084] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 2 h at a heating rate of 5 °C / min.

[0085] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0086] Example 9 According to the flow chart shown in Figure 1, the waste titanium dioxide carrier is used to prepare the photocatalyst Cu-TiO2 for hydrogen production by water splitting. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of waste SCR catalyst, perform ultrasonic treatment multiple times under strong ultrasonic conditions, with an ultrasonic input power of 400 W, and dry the clean waste titanium dioxide carrier in a blast dryer for 24 hours. After testing, based on the total weight of the waste titanium dioxide carrier, the composition of the clean waste titanium dioxide carrier is as follows: 86.22% titanium dioxide, 2.32% aluminum oxide, 3.15% silicon dioxide, 3.48% tungsten trioxide, 2.43% iron oxide, 2.19% calcium oxide, and 0.21% vanadium pentoxide.

[0087] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0088] (3) Weigh 8 mg of anhydrous cupric chloride and add it to 100 ml of deionized water to form a copper ion solution. Add 1 g of spent titanium dioxide carrier and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0089] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0090] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis. The temperature was set to 550 °C, the holding time was 2 h, and the heating rate was 5 °C / min.

[0091] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0092] Comparative Example 1 The preparation steps are the same as those in Example 1, except that no copper source is added. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of waste titanium dioxide carrier, perform ultrasonication for multiple times under strong ultrasonic conditions, and the ultrasonic input power is 400 W. After drying in a blast dryer for 24 h, a clean waste titanium dioxide carrier is obtained, and the chemical composition is the same as that in Example 1.

[0093] (2) The waste titanium dioxide carrier is ground into fine powder by ball milling, and the ball-to-material ratio is set to 8:2. After the ball milling, the material is sieved through a 325-mesh sieve.

[0094] (3) The obtained white product was stored in a drying oven and dried overnight at 70°C for 24 h.

[0095] (4) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis. The temperature was set to 500 °C, the holding time was 3 h, and the heating rate was 3 °C / min.

[0096] (5) Grind the powder obtained after high-temperature pyrolysis in a mortar for 30 minutes to obtain a TiO2 catalyst.

[0097] Comparative Example 2 The preparation steps are the same as those in Example 1, except that commercial titanium dioxide is used and a copper source is added. The specific steps are as follows: (1) Weigh 200 ml of deionized water, add 5 g of commercial titanium dioxide, and perform ultrasonication for multiple times under strong ultrasonic conditions with an ultrasonic input power of 400 W. Dry the clean titanium dioxide carrier in a blast dryer for 24 h.

[0098] (2) Grind the commercial titanium dioxide into fine powder by ball milling, with the ball-to-material ratio set at 8:2. After ball milling, sieve the material through a 325-mesh sieve.

[0099] (3) Weigh 8 mg of anhydrous cupric chloride and add it to 100 ml of deionized water to form a copper ion solution. Add 1 g of commercial titanium dioxide and stir at 600 r / min for 4 h. Centrifuge and wash in a high-speed centrifuge to obtain a light green product. The centrifuge speed is set to 10,000 r / min and the centrifugation time is 5 min.

[0100] (4) The obtained light green product was stored in a vacuum drying oven and dried overnight at 70 °C for 24 h.

[0101] (5) The dried product was ground for 30 min and placed in a muffle furnace for high-temperature pyrolysis at 500 °C for 3 h at a heating rate of 3 °C / min.

[0102] (6) The powder obtained after high-temperature pyrolysis was ground in a mortar for 30 min to obtain a Cu-TiO2 catalyst.

[0103] Comparative Example 3 Commercial titanium dioxide was used without added copper sources. The properties of the catalyst material prepared in this example are shown in Table 1.

[0104] Comparative Example 4 The preparation steps are the same as those in Example 1, except that the grinding step in step (6) is omitted.

[0105] Comparative Example 5 The preparation steps are the same as those in Example 1, except that the grinding step in step (5) is omitted.

[0106] Comparative Example 6 The preparation steps are the same as those in Example 1, except that the heating rate in step (5) is adjusted to 2°C / min.

[0107] Comparative Example 7 The preparation steps are the same as those in Example 1, except that the insulation time in step (5) is adjusted to 4 h.

[0108] Comparative Example 8 The preparation steps are the same as those in Example 1, except that the anhydrous cupric chloride in step (3) is adjusted to cupric nitrate trihydrate.

[0109] Test Case The photocatalytic water splitting hydrogen production activity of the catalyst materials in the above embodiments and comparative examples was tested under the following test conditions: methanol was used as a sacrificial agent in the test process. 20 mg of the catalyst was evenly dispersed in a reactor containing 80 mL of a mixed solution of water and methanol (H2O: methanol = 4:1, volume ratio), and argon was used as a carrier gas and methanol as a sacrificial agent for the hydrogen production process. The reaction was carried out after vacuum stirring for half an hour before the reaction. When the reactor vacuum indication was equal to 0.3 KPa, the photocatalytic hydrogen production test was started, effectively eliminating the influence of air. The experiment was completed under xenon lamp irradiation conditions.

[0110] Figure 5This is the instantaneous photocurrent response diagram of the Cu-TiO2 catalyst material prepared in Example 1 under xenon lamp conditions. It can be seen that the light response intensity of Cu-TiO2 is higher than that of commercial TiO2 (Comparative Example 3), which proves that Cu-TiO2 has excellent electron transfer ability. In addition, Figure 5 As shown, the photocurrent spectrum analyzes the photoelectric properties of Cu-TiO2 and TiO2 materials by measuring the current generated by them under illumination conditions. The photocurrent intensity generated by the material under illumination can determine the separation and transmission characteristics of photogenerated carriers, thereby proving the existence of Schottky junction. Schottky heterojunction causes the photogenerated carriers of Cu-TiO2 to be effectively separated, so the photocurrent response intensity of Cu-TiO2 is higher than that of TiO2.

[0111] Figure 6 The hydrogen production performance diagram of each catalyst under the full spectrum condition of 300w xenon lamp is shown in Figure 2. Figure 6 It can be seen that the hydrogen production rate of the spent TiO2 carrier (Comparative Example 1) is only 56 μmol g -1 h -1 The hydrogen production rate of commercial titanium dioxide (Comparative Example 3) is 211 μmol g -1 h -1 , while the hydrogen production rate of Cu-TiO2 (Example 1) is 308 μmol g -1 h -1 , which is 1.46 times that of commercial titanium dioxide, and the material has good hydrogen production performance. The hydrogen production rates of various embodiments and comparative examples are shown in Table 1.

[0112] Table 1 Hydrogen production rates of catalysts of Examples and Comparative Examples

[0113] Compared with the catalyst sample shown in Comparative Example 1, a copper source is added to the catalyst in Example 1. From the comparison results of Example 1 and Comparative Example 1 in Table 1, it can be seen that the hydrogen production efficiency of Example 1 is greatly improved, because the doping of copper species improves the ability of the waste titanium dioxide support material to dissociate water, broadens the light absorption range of the waste support, improves the carrier migration ability, and enhances the reaction kinetics.

[0114] The catalyst sample shown in Comparative Example 2 uses commercial titanium dioxide to add a copper source, and Comparative Example 3 uses commercial titanium dioxide. From the comparison results of Example 1 and Comparative Examples 2-3 in Table 1, it can be seen that the hydrogen production efficiency of Example 1 is 1.46 times that of commercial titanium dioxide, and the hydrogen production efficiency is greatly improved. The present invention can make full use of the high-value titanium resources in the waste SCR catalyst.

[0115] Compared with the catalyst sample shown in Comparative Example 4, the catalyst in Example 1 has an additional grinding step in step (6). From the comparison results of Example 1 and Comparative Example 4 in Table 1, it can be seen that the grinding step can increase the specific surface area of ​​the material, reduce agglomeration, and provide more active sites, thereby improving the photocatalytic efficiency and hydrogen production efficiency.

[0116] Compared with the catalyst sample shown in Comparative Example 5, the catalyst in Example 1 has an additional grinding step in step (5). From the comparison results of Example 1 and Comparative Example 5 in Table 1, it can be seen that the grinding step helps to obtain a uniform heating effect and chemical reaction in the subsequent calcination process, thereby improving the hydrogen production efficiency of the catalyst.

[0117] Compared with the catalyst sample shown in Comparative Example 6, the heating rate of the catalyst in Example 1 was adjusted. From the comparison results of Example 1 and Comparative Example 6 in Table 1, it can be seen that a too low heating rate is not conducive to the hydrogen production rate of the catalyst, because a too slow heating rate may affect the oxidation rate of the material surface.

[0118] Compared with the catalyst sample shown in Comparative Example 7, the catalyst in Example 1 has adjusted the holding time. From the comparison results of Example 1 and Comparative Example 7 in Table 1, it can be seen that too long a holding time is not conducive to the hydrogen production rate of the catalyst, because too long a holding time may lead to excessive diffusion of copper species in titanium dioxide, which may form larger copper clusters or copper particles, thereby reducing the specific surface area and activity of the catalyst.

[0119] Compared with the catalyst sample shown in Comparative Example 8, the type of copper salt is adjusted in the catalyst of Example 1. From the comparison results of Example 1 and Comparative Example 8 in Table 1, it can be seen that the copper salt in the present invention is preferably copper chloride or its hydrate.

[0120] In summary, the Cu-TiO2 photocatalytic hydrogen production material prepared by in-situ repair of waste TiO2 carriers according to the present invention has superior hydrogen production performance compared to undoped waste TiO2 carrier materials and pure commercial titanium dioxide. The overall scheme is green and pollution-free, with low raw material cost, high utilization rate, low energy consumption, good effect, and is suitable for large-scale preparation.

[0121] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing a photocatalytic water splitting hydrogen production catalyst using waste titanium dioxide carrier, characterized in that: The steps include: S1, immersing the waste titanium dioxide carrier in an aqueous solution of a divalent copper salt and stirring the solution to allow copper to be adsorbed on the surface of the carrier; Wherein, the mass percentage of TiO2 in the waste titanium dioxide carrier is greater than 85%; S2. The product obtained in step S1 is subjected to pyrolysis treatment to obtain the photocatalytic water decomposition hydrogen production catalyst.

2. The method for preparing a photocatalytic hydrogen production catalyst using waste titanium dioxide carrier according to claim 1, characterized in that: The waste titanium dioxide carrier comes from waste SCR catalyst; preferably, the waste titanium dioxide carrier is obtained according to the following steps: ultrasonically washing, drying and ball milling the waste SCR catalyst in sequence; The particle size of the waste titanium dioxide carrier is ≤45um.

3. The method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 2, characterized in that: The mass percentage of Al2O3 in the waste titanium dioxide carrier is less than 6.0%.

4. The method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 3, characterized in that: The divalent copper salt is a water-soluble copper salt, preferably copper chloride or its hydrate, more preferably at least one of anhydrous copper chloride, copper chloride monohydrate, and copper chloride dihydrate.

5. The method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 4, characterized in that: The mass ratio of the waste titanium dioxide carrier to the divalent copper salt is 1:(0.005-0.03).

6. The method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 5, characterized in that: The stirring process is carried out at a rotation speed greater than 500 r / min and for a time greater than 3 hours.

7. The method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 6, characterized in that: The method comprises the following steps after the stirring treatment: centrifuging the stirred mixture to collect the solid phase, and then washing and drying the solid phase; preferably, the drying is vacuum drying at 70° C. for 12 to 24 hours.

8. The method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 7, characterized in that: The method further comprises the step of grinding the product obtained in step S1 before the pyrolysis treatment, preferably grinding for 0.5 to 1 hour; The pyrolysis treatment is carried out in an air muffle furnace, the temperature is raised to 500-550° C. at a heating rate of 3-10° C. / min, and the holding time is 1-3 hours; The method further comprises the step of grinding the pyrolysis product after the pyrolysis treatment, preferably grinding for 0.5 to 1 hour.

9. The photocatalytic hydrogen production catalyst prepared by the method for preparing a photocatalytic hydrogen production catalyst using a waste titanium dioxide carrier according to any one of claims 1 to 8.

10. A method for producing hydrogen by photolysis of water, characterized in that: The method comprises the following steps: using the photocatalytic hydrogen production catalyst according to claim 9 as a catalyst to produce hydrogen by photolysis of water.

Citation Information

Patent Citations

  • Method for separating and recovering titanium dioxide from waste SCR denitrification catalyst

    CN106745230A

  • Method for recycling titanium dioxide from waste SCR catalyst

    CN108773851A

  • Preparation method and application of high-dispersion copper-loaded titanium dioxide nanosheet

    CN112439416A

  • Cu cluster loaded TiO2 water treatment catalyst as well as preparation method and application thereof

    CN113731414A

  • Method for preparing self-doped titanium-niobium-oxygen negative electrode material by using waste titanium dioxide carrier, negative electrode material and lithium ion battery

    CN116947099A